156. How Does Exposure to C. Diffogenic Antibiotics Impact Multidrug-resistant Organism Colonization and Environment Contamination in Nursing Homes?. (31st December 2020) - Gontjes, Kyle J; Gibson, Kristen; Lansing, Bonnie; Mantey, Julia; Jones, Karen; Cassone, Marco; Wang, Joyce; Mills, John; Mody, Lona; Patel, Payal K
Abstract: Background: Antimicrobial stewardship program (ASP) outcomes are often measured in the acute care setting, less is known about the effect of acute care antibiotic exposures on multidrug-resistant organism (MDROs) colonization of nursing home (NH) patients. We assessed exposure to antibiotics commonly associated with Clostridioides difficile (C. diffogenic agents) on post-acute care patient colonization and room environment contamination (Figure 1). Figure 1. Conceptual Diagram of Hospital Antibiotic Exposure's Influence on Patient Colonization and Room Environment Contamination with Multidrug-Resistant Organisms Methods: MDRO surveillance of post-acute care patients in 6 NHs between 2013–16. We screened patient hands, nares, oropharynx, groin, perianal area, and high-touch room environment surfaces for methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and resistant Gram-negative bacilli (rGNB). C. diffogenic agents were defined as fluoroquinolones, 3 rd /4 th generation cephalosporins, penicillin combinations, lincosamides, and carbapenems. Multivariable logistic regression was used to assess whether hospital antibiotic exposure is an independent risk factor for MDRO colonization and room environment contamination on study enrollment. Results: We enrolled 618 patients: average age was 74.4 years; 57.4% female; 62.3% white; 9.9% had indwelling devices (Table 1). Three hundred-fifty patients (56.6%) were MDRO colonized on enrollment: 98 (15.9%), MRSA; 208 (33.7%); VRE; 196 (31.7%), rGNB. Sixty-eight percent of patient rooms were MDRO contaminated: 166 (26.9%), MRSA; 293, (47.4%). VRE; 182 (29.5%), rGNB. A majority (59.4%) of patients were exposed to an antibiotic before admission. Of which, 239 (65.1%) were exposed to a C. diffogenic antibiotic. In multivariable analysis, C. diffogenic antibiotic exposure was an independent risk factor for MDRO colonization (OR, 1.94; 95% CI, 1.35–2.79), MDRO room environment contamination (OR, 1.94; 95% CI, 1.43–2.63), VRE colonization (OR, 4.23; 95% CI, 2.59–6.90), and VRE room environment contamination (OR, 2.58; 95% CI, 2.00–3.33). Table 1. Clinical Characteristics and MDRO Burden on Study Enrollment, Stratified by Hospital Antibiotic Exposure Status Multivariable Analysis of Hospital Antibiotic Exposure Status as Risk Factor for Proximal and Distal MDRO Outcomes Conclusion: Hospital exposure to antibiotics is associated with an increased risk of VRE colonization and room environment contamination on NH study enrollment. These observations highlight the potential influence of hospital-based ASPs on MDRO prevalence and transmission in NHs. Disclosures: All Authors : No reported disclosures